Propuesta didáctica para el fortalecimiento de la dimensión socioafectiva en pro del desarrollo de la Inteligencia Emocional en los niños y niñas del grado preescolar del Centro Etnoeducativo Nº 9 de Riohacha - Guajira (2021)
The didactic proposal is the result of establishing a series of activities that favor the development and strengthening of emotional intelligence. This entails great challenges for the community in general, but mainly for parents, since it implies important changes in the way of educating their children, and in turn, in the role of children, since they must reflectively position themselves in its growth and development. The present research aims to strengthen the socio-affective dimension through a didactic proposal based on the guiding activitiesin favor of the development of Emotional Intelligence in preschool students.